Development or absence of conjugate fractures in low-permeability sandstones - Yang, Haimeng; Yu, Jifeng; Chen, Peng; Hu, Caifu; Dai, Peng (Frontiers in Earth Science, 2023)
Natural fractures are ubiquitous in rocks. The Coulomb law of Mohr's failure theory predicts that the angle between conjugate failure surfaces is a constant. In the Ordos Basin, observing the development of two groups of conjugate fractures in the field, cores and imaging logging is very difficult. In this paper, the directions of paleocurrents in the Upper Triassic Yanchang Formation of the Ordos Basin are determined by measuring the orientations of field bedding. Through the correlation analysis of paleocurrent and natural fracture orientations, when the sediment comes from a single source, a group of fractures with a large angle between conjugate fractures and paleocurrent direction is found not to develop. When the sediments in the study area have two provenances, both provenance directions affect the development of conjugate fractures. In the southern Ordos Basin, influenced by the direction of paleocurrent flow in the near-north direction, fractures in the near N-S direction develop. Through rock mechanics experiments in different directions, the planar anisotropy in rock mechanics parameters caused by the direction of paleocurrent flow is found to be the geological factor leading to various degrees of fracture development in different directions within the Ordos Basin.